“Sendiko Dawuh Ngarso Dalem” (Studi Kasus Makna Kerja pada Abdi Dalem Punakawan di Keraton Ngayogyakarta Hadiningrat) - Pradita Nindya Aryandha; Zainal Mustafa Elqadri (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2020)
This research is titled Sendiko Dawuh Ngarso Dalem (Case Study of Punokawan Courtiers in Keraton Ngayogyakarta Hadiningrat). The purpose of this research is to understand the framework of the maning Punokawan Courtiers?s work in Keraton Ngayogyakarta Hadiningrat after obtaining a salary sourced the Yogyakarta Privileges Fund. This research is considered as qualitative research with case study approach. This research uses interview as data collecting method. The informants in this study are Dr. Threresia Suharti, S.S.T., M.S and Drs. Antonius Sutarno, who work as Punakawan Tepas and Caos Courtiers who has served for more than 30 years. In order to know data validation, it is therefore using credibility test and transferability test. Data test method uses triangulation, whereas data analysis method uses reduction data, display data, and conclusion drawing/verification. This research found that the maning of work for the courtiers was interpreted as a calling.